Identification of The Eclectic Identity of Architectural Diversity Through Cognitive Mapping to Shape The Image of The Area and The Built Environment on Bangka Island - Fahri, Muhammad; Arlianda, Reza; Rahmadyani, Helfa; Felly, Rizka; Syafrina, Andina (Universitas Muhammadiyah Surakarta, 2026)
Globalization poses a risk of homogenizing urban architectural identities, threatening cities with eclectic heritage such as Pangkalpinang, which reflects the acculturation of Malay, Chinese, and Colonial cultures. This study aims to identify the physical elements that shape the city image through a cognitive mapping method validated quantitatively. Using a sequential exploratory mixed-method design, the research begins with a qualitative stage involving participatory mapping to identify urban elements based on Kevin Lynch’s theory (path, edge, district, node, landmark). This stage is followed by a quantitative interactive survey using GeoGuessr involving 50 respondents to measure the accuracy of spatial perception. The findings indicate that landmarks and nodes have the highest levels of spatial recognition, serving as key cognitive anchors for the community. In contrast, paths and edges show more fragmented perceptions and lower accuracy levels. This research contributes a new, more objective methodology for interpreting the city image and provides empirical data applicable to the development of urban design guidelines and heritage preservation strategies based on collective perception.